(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The main purpose of the study was to analyse the farmers communication exposure and knowledge in poultry farming. The research was conducted in three selected unions of Bhaluka upazila under Mymensingh district. Each of the six selected characteristics of poultry farmers namely age, education, family size, family education, farm size and organizational participation are the independent variables; while farmers exposure to communication media for poultry production and farmers knowledge on poultry were the two dependent variables. In case of farmers exposure to communication media for poultry production, majority of the farmers (54 percent) had low exposure to communication media, while 46 percent had medium exposure and none of them had high exposure. In the case of poultry farming knowledge, majority of the farmers (57 percent) had medium knowledge while 29 percent of them had low knowledge and only 14 percent had high knowledge. Tests of hypotheses indicated that education of the farmers was positively related to communication exposure for poultry production while the rest independent variables had no relationship with any of the dependent variables. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19842 J. Bangladesh Agril. Univ. 11(2): 177-182, 2013